Efficacy of intrathecal baclofen bolus on neuropathic pain in patients with spinal cord injury: A protocol for systematic review and meta-analysis - Wang, Shou-feng (Medicine (Baltimore), 2020)
BACKGROUND: This study will explore the efficacy and safety of intrathecal baclofen bolus (IBB) on neuropathic pain (NPP) in patients with spinal cord injury (SCI). METHODS: All potential literatures of IBB on NPP in patients with SCI will be searched from the following electronic databases from inauguration to the January 31, 2020: PUBMED, EMBASE, Cochrane Library, Web of Science, Chinese Scientific Journal Database Information, WANGFANG, and China National Knowledge Infrastructure. In addition, we will search other sources, such as dissertations and reference lists of included trials. There are no restrictions of language and publication status in searching all literature sources. The quality of each eligible trial will be assessed using Cochrane risk of bias tool, and publication bias will be checked using a funnel plot and Egger test. Statistical analysis will be conducted using RevMan 5.3 software. RESULTS: This study will scrutinize the efficacy and safety of IBB on NPP in patients with SCI through pain intensity of NPP, spasticity, walking ability, health-related quality of life, duration of stay at hospital (days), incidence of adverse event, and mortality rate. CONCLUSIONS: The findings of this study will present helpful evidence to judge whether IBB is effective on NPP in patients with SCI or not. STUDY REGISTRATION NUMBER: INPLASY202040192.